A STUDY ON POLICY HOLDERS SATISFACTION ON SERVICES TOWARDS SBI LIFE INSURANCE - MAHESWARI, Dr.V (International Journal of Psychosocial Rehabilitation, 2020)
This study explores satisfaction level of policy holders towards SBI life insurance in Chidambaram town. Due to increasing awareness among people about their uncertainty of life and increasing competition in insurance sector, it is significant for insurance companies to understand the requisite of their policy holders. This main aim of this study is to know the consumer satisfaction towards SBI.This study is based on primary data which is collected through questionnaire among 100 policy holders in Chidambaram and data were analysed with multi variety statistical tools like percentage and chi-square analyses and weighted score analyses were used to identify the factors responsible for policy holder satisfaction on services towards SBI lifeinsurance